“Técnica de Jacobson en la Psicoprofilaxis del parto” - Dayana Tamara, Mariño Vallejo (2020)
Pregnancy is a complex process where the development of various physiological, metabolic and morphological changes are carried out in the pregnant women, being able to become an overwhelming and emotional process. Walker mentions, that the intensity of lumbopelvic pain during pregnancy increases with time, during the day and throughout its development, especially at week 36. The objective of this study is to demonstrate the effectiveness of psychoprophylaxis during pregnancy, so a previous bibliographical research was developed on the benefits of this method, both to the pregnant woman and to her child. It is an observational and descriptive study, since it allows the collection of data from the gestation process, seeking to corroborate the effects of the method, through assessment scales, surveys and direct observation of its effectiveness. The results showed that this process had a favorable influence on more than half of the patients, both on normal delivery, on labor time and labor pain, urinary incontinence and improvement in pelvic floor condition, Therefore it was possible to conclude that if technical of JACOBSON is efecct in the psychoprophylaxis of pregnancy is effective in several areas of pregnancy.